Simplified calculation of fire resistant temperature for cold-formed steel load-bearing composite walls. (December 2020) - Ye, Jihong; Chen, Wenwen
Abstract: The research on the fire resistance design of cold-formed steel (CFS) load-bearing composite walls, as the main vertical load-bearing and space-dividing components of the CFS structure, has received widespread attention. The purpose of this article is to propose a formula for calculating the fire resistant temperature of CFS composite walls in order to simplify the design method. Three different configurations for composite wall lined with gypsum plasterboards which commonly used were chosen as research objects. According to the temperature-rise rule and heat transfer mechanism, the temperature-rise curves at hot flange of the studs were obtained. Then a heat transfer model was established with considering both the heat conduction and cavity radiation where obtained temperature load was applied at hot flange of the stud to calculate the temperature distribution of the wall cross-section. The improved heat transfer model not only considered the effect of cavity radiation, but also simulated the direct exposure of the stud to high temperature due to the falling-off or losing of insulation for sheathed board. Then the heat transfer calculation results were imported into a simplified mechanical model for thermal–mechanical coupling numerical simulation. Integrity, insulation, and the load bearing capacity of the stud cross section were taken as the comprehensive consideration criteria for composite wall failure. The temperature at hot flange of the stud was defined as fire resistant temperature when the composite wall damaged. Finally, load ratio and fire resistance temperature related calculation formulas were fitted from the results of transient thermal–mechanical coupling simulation with varying load ratios. The comparison of fire resistance temperature between fitting formula and fire test results verified the applicability of the proposed fire resistance temperature calculation formula. Compared with the fire resistance temperature calculation formulas in the existing literature, the calculation formula proposed in this paper was more accurate and reasonable.